Japan and the Pacific, and a Japanese view of the Eastern question - Inagaki, Manjiro (T. Fisher Unwin, 1890)
In books where there are images such as portraits, maps, sketches etc We have endeavoured to keep the quality of these images, so they represent accurately the original artefact. Although occasionally there may be certain imperfections with these old texts, we feel they deserve to be made available for future generations to enjoy.